Pengaruh Volume Penjualan Saham Dan Tingkat Suku Bunga SBI Terhadap Return Saham Pada PT Indocement Tunggal Prakarsa, Tbk - Asmirah, St; Nurulrahmatiah, Nafisah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
The purpose of this study is to determine the effect of share sales volume and SBI interest rates on stock returns at PT Indocement Tunggal Prakarsa, Tbk. This study uses a quantitative approach because it uses data in the form of numbers. The type of data used is secondary data obtained from the official website (http://www.indocement.co.id) The population in this study is data on sales volume, interest rates and stock returns for 30 years, from 1989-2019. using a sample for 15 years, namely from 2004-2018. The sampling method used was purposive sampling method. Methods of data collection using the method of documentation and study libraries. The data analysis tool used is multiple linear regression with the help of the SPSS version 21.0 program. The results of this study indicate that there is a partially significant effect between share sales volume and stock returns at PT Indocement Tunggal Initiative, Tbk. Tbk. The magnitude of the influence of share sales volume and interest rates on stock returns at PT Indocement Tunggal Initiative, Tbk is 200% and the remaining 79.9% is influenced by other factors not examined in this study